Pemasaran Sosial Media dan Pengembangan Produk pada Pelaku UMKM Makanan di Carocok Pesisir Selatan - Dwita, Vidyarini; Septrizola, Whyosi; Hasmira, Mira Hasti (Universitas Negeri Padang, 2023)
Large- and small-scale enterprises have a growing need to expand marketing access by employing social media as a platform for selling and product development to increase sales. Community service activities were conducted in Carocok, Pesisir Selatandistrict, West Sumatra, with the participation of fifteen seafood-related business actors. The Community Service team provides SME business owners with training and expertise regarding marketing access on social media and product development to enhance sales and maximize profitability for MSME owners in the food business that process marine raw materials. The outcomes of service activities supply business owners with the knowledge necessary to formulate marketing strategies, particularly social media marketing and product development.